Optimizing Physical Activity for Glycemic Control in Type 1 Diabetes: Strategies and Risks - Przybysz, Paulina; Kucharska, Maja; Kruszewski, Adrian; Szyszka, Monika; Kwiliński, Kacper; Paduszyńska, Natalia; Dąbrowska, Anna; Błaszczak, Karolina; Wawrzyńska, Barbara (Quality in Sport, 2024)
Type 1 diabetes mellitus (T1DM) is a chronic autoimmune condition characterized by the destruction of insulin-producing beta cells in the pancreas, necessitating lifelong insulin therapy. This study explores the impact of physical activity on glycemic control and overall health in individuals with T1DM. Despite its proven benefits, including improved cardiovascular health, lower HbA1c levels, and reduced insulin requirements, over 60% of T1DM patients do not engage in regular exercise. Different types of physical activities—such as aerobic, anaerobic, and high-intensity interval training (HIIT)—affect metabolic responses differently. Aerobic exercises and HIIT have shown significant improvements in health-related quality of life (HRQoL) and reduced incidence of severe complications, such as diabetic ketoacidosis. However, exercise-induced hypoglycemia remains a significant risk, especially if exercise follows recent severe hypoglycemic episodes. Proper management strategies include adjusting insulin doses, monitoring glucose levels, and carbohydrate intake. The study highlights the importance of tailored exercise plans and preventive measures to mitigate risks such as nocturnal hypoglycemia and elevated ketones. Ultimately, effective integration of physical activity into diabetes management can lead to enhanced overall health and quality of life for individuals with T1DM.